PENGEMBANGAN EKOSISTEM INOVASI DI KOTA CIMAHI MELALUI CIMAHI TECHNO PARK - Widya Retno, Herni
Many experts consider innovation is significant for economic development. Technopark is an example of the policies to form a conducive ecosystem for innovation. Through a Presidential Regulation in Science and Technology Parks, Indonesia encouraged the establishment of 100 technoparks in 2015, including Cimahi Techno Park (CTP). This study aims to apprehend the experience of the Cimahi City Government in developing an innovation ecosystem through the Cimahi Techno Park. The research objectives are to identify the Cimahi Techno Park development process, analyze the role of Cimahi Techno Park in the development of the Cimahi City innovation ecosystem, and discover the distinctive experience of the Cimahi City Government in developing the innovation ecosystem through the Cimahi Techno Park. The research methodology used is qualitative research with case studies. The researcher collected primary data by observing and conducting semi-structured interviews with stakeholders involved in developing the Cimahi Techno Park. Government documents, news and related journals were used as secondary data. From the conclusions, it can be seen that there have been transformations both in terms of institutions, functions, activities and linkages with other elements in the innovation ecosystem of Cimahi City, which indicate the development of Cimahi Techno Park. The role of Cimahi Techno Park in developing the Innovation Ecosystem of Cimahi City can be observed in the programmes and policies implemented by the CTP, which are more oriented towards incubating businesses and providing co-working space. The functions and activities of the Cimahi Techno Park institution contribute to connecting actors (stakeholders) and artefacts (services and technologies) in innovation networks, thus achieving innovation output, especially in the form of programme innovation and business incubation. While incubating is necessary for the innovation process, innovation activities do not necessarily occur at CTP because there are no programmes and activities that play a significant role in turning innovative products into commercial products. In addition, there are limitations of the CTP to actively encourage the involvement of existing innovation actors. The institutional governance at Cimahi Municipality has the potential to alter the innovation networking thus have an